Design Unique Air‐Stable and Li–Metal Compatible Sulfide Electrolyte via Exploration of Anion Functional Units for All‐Solid‐State Lithium–Metal Batteries. (14th April 2022) - Ahmad, Niaz; Sun, Shaorui; Yu, Peiwen; Yang, Wen
Abstract: The marriage of solid‐state sulfide electrolytes (SSSEs) with Li‐anode and oxide‐based cathodes can multiply the energy density of all‐solid‐state Lithium–metal batteries (ASSLMBs). However, hydrolysis in the air, reduction at the Li/SSSE interface, and growth of Li‐dendrites inside SSSEs collectively block the route of sulfide‐based ASSLMBs. Herein, a novel Li2.96 P0.98 S3.92 O0.06 ‐Li3 N glass–ceramic electrolyte (GCE) is developed, wherein O and N substitution produce POS3 3– and Li3 N unique functional units enable superior σLi+ 1.58 mS cm –1 at RT. Notably, POS3 3– units in Li2.96 P0.98 S3.92 O0.06 ‐Li3 N excellently prevent the structural degradation against moisture @45–50%. The critical current density of Li2.96 P0.98 S3.92 O0.06 –Li3 N reaches 1 mA cm –2 /1 mAh cm –2 @ RT. Moreover, Li//Li cells realize unprecedented Li‐plating/stripping >1000 h at 0.3 mA cm –2 /0.3 mAh cm –2 and 0.5 mA cm –2 /0.5 mAh cm –2 at RT. ToF‐SIMS and depth‐X‐ray photoelectron spectroscopy (XPS) confirm the formation of Pre‐solid‐electrolyte interphase (SEI) enriched with thermodynamically stable Li2 O and Li3 N species at Li/Li2.96 P0.98 S3.92 O0.06 –Li3 N interface, suppressing the interfacial reactions and growth of Li‐dendrites inside Li2.96 P0.98 S3.92 O0.06 –Li3 N. Furthermore, LiNbO3 @NCA/Li2.96 P0.98 S3.92 O0.06 –Li3 N/Li cells deliver a remarkable initial discharge capacity of 177.3, 177.6, and 177.8 mAh g –1 with 7.50, 16.50, and 21.50 mg cm –2 of NCA loading. Thus, the novel Li2.96 P0.98 S3.92 O0.06 –Li3 N GCE addresses all key challenging issues and has tremendous potential to be used in sulfide‐based high‐energy ASSLMBs. Abstract : O and N substitution produces ultrastable POS3 3– and Li3 N unique functional units, wherein POS3 3‐ intrinsically enhance the structural stability of Li2.96 P0.98 S3.92 O0.06 –Li3 N glass–ceramic and suppresses the generation of toxic H2 S in the ambient environment. Furthermore, O and N leads to the Pre‐solid‐electrolyte interphase (SEI) enriched Li2 O, and Li3 N species realize stable and reversible Li‐stripping/plating for Li//Li cells beneficial for all‐solid‐state lithium–metal batteries.